(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the article, the purpose of analyzing a sentence in terms of semantics is to determine how the meaning of the sentence is organized and what the mutual connections between its semantic components are.